Natural Variation in OsMKK3 Contributes to Grain Size and Chalkiness in Rice - Pan, Yinghua; Chen, Lei; Zhao, Yan; Guo, Haifeng; Li, Jingcheng; Rashid, Muhammad Abdul Rehman; Lu, Chunju; Zhou, Weiyong; Yang, Xingka; Liang, Yuntao; Wu, Hao; Qing, Dongjing; et al. (Frontiers in Plant Science, 2021)
Rice (Oryza sativa L.) is an important staple food crop for more than half of the world’s population. Enhancing the grain quality and yield of rice to meet growing demand remains a major challenge. Here, we show that OsMKK3 encode a MAP kinase kinase that controls grain size and chalkiness by affecting cell proliferation in spikelet hulls. We showed that OsSPL16, GS5, and GIF1 have a substantial effect on the OsMKK3-regulated grain size pathway. OsMKK3 has experienced strong directional selection in indica and japonica. Wild rice accessions contained four OsMKK3 haplotypes, suggesting that the OsMKK3 haplotypes present in cultivated rice likely originated from different wild rice accessions during rice domestication. OsMKK3-Hap1, gs3, and gw8 were polymerized to enhance the grain length. Polymerization of beneficial alleles, such as OsMKK3-Hap1, gs3, gw8, fgr, alk, chalk5, and wx, also improved the quality of hybrid rice. Overall, the results indicated that beneficial OsMKK3 alleles could be used for genomic-assisted breeding for rice cultivar improvement and be polymerized with other beneficial alleles.